Mengatasi Perundungan (Bullying) di Kalangan Siswa Berbasis Pendidikan Akhlak al-Ghazali - Euis Latipah; Abdillah abdillah; Saehudin Saehudin (STAI Al-Mas'udiyah, 2025)
This study aims to analyze al-Ghazali's moral education and its correlation in an effort to prevent reprehensible behavior among students or adolescents. This research method uses a qualitative type with a literature study approach. Data was collected through a literature review related to related fields of research, namely the concept of al-Ghazali's morals. The data that has been collected is then analyzed and concluded. The results of the study conclude that Al-Ghazali presents morality not as the ultimate goal of human beings to live, but as a tool to support the best functioning of the soul to attain the highest truth. Al-Ghazali argued that morality is not just an action, but the ability to do. However, morality must be associated with a mental situation that is ready to act, and it must be associated with this situation so that the resulting behavior becomes a daily habit. A person's bad character can basically be transformed into a noble character, for example from cruel to compassionate. Adolescent uncommendable behaviors such as fights, fights and bullying must first be eliminated and then students are equipped with commendable attitudes such as compassionate, patient, gentle, able to control anger, and respect for humanity